REQUESTS IN EFL: INTERLANGUAGE PRAGMATIC STUDY ON INDONESIAN LEARNERS OF ENGLISH - Hadi Susilo, Welas (Kajian Linguistik dan Sastra, 2015)
This paper is a part of a larger scale of interlanguage pragmatic study on Indonesian EFL learners in expressing request strategies. The research participants were forty students of Junior High School in Central Java, Indonesia. Data for this study were elicited from the respondents by written Discourse Completion Tasks (DCT), which consisted of nine situations in different social situations. The findings of the study showed the EFL learners employed both direct and indirect strategies of requests. Nevertheless, they mostly utilized conventionally indirect (hearer-oriented condition) strategies in the form of ability/willingness/ permission. Regarding direct request, they employed obligatory, performative and imperative requests. It was also found that the more familiar the interlocutors the more direct they will make requests.Keywords: request strategies, interlanguage pragmatics, indirectness, directnessAbstrak